ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEINGINAN WAJIB PAJAK DALAM MENGGUNAKAN E-FILING DI KOTA BATAM - Situmorang, Dokman Marulitua; Rahmawati, Yuli (Journal Accounting International Mount Hope, 2023)
The research objective is whether there is an impact of perceived usefulness ontaxpayers' interest in using e-filing? Is there an impact of perceived convenience ontaxpayers' interest in using e-filing? Is there an impact of information technologyreadiness on taxpayers' interest in using e-filing? The method used is to compare thenumber of taxpayers in 2019 and 2020. The population in this study is all individualtaxpayers in Batam City. The sample was determined randomly from various taxpayerrespondents who had used the e-filing system. The results of this study show thatPerception of Usefulness, Perception of Ease, and Readiness of Information Technologyinfluence Taxpayers' Interest in Using the e-filing system